TERMINOLOGI DASAR PADA HIMPUNAN SIMETRISASI ALJABAR MIN-PLUS - Suroto; Ari Wardayani; Chumaedi Sugihandardji (LPPM Universitas Terbuka, 2022)
This paper discusses some of the terminology and basic properties of the set of min-plus algebra symmetrization. The results are algebraic structure of the positive or zero part of the set of min-plus algebra symmetrization is a semi-field, and the min-plus algebra can be viewed as the positive or zero part in the context of the set of min-plus algebra symmetrization. Furthermore, the form of the result of the subtraction of the elements in the set of min-plus algebra symmetrization, the multiplicative inverse of element in the non zero-positive and negative part, and some basic properties of balance as an analogy to the similarity of linear algebra are also obtained.